Caracterização sistemática do aquífero serra grande na porção Nordeste da Bacia Sedimentar do Parnaíba - Aguiar, Roberio Boto de (2017)
This research intends to extend the knowledge about the groundwater of the Serra Grande aquifer, specifically, in the northeastern portion of the Parnaíba sedimentary basin, aiming to identify the various subsystems and their interactions, responsible for the characteristics of the aquifer system. The study began by surveying of existing knowledge through bibliographical research about geological and geometrical characterization of this portion of the basin. 80 electric vertical soundings were performed, which investigated up to 750 m deep, and detected two aquifer zones separated by a resistive layer. The interpretations of these surveys estimate that the more frequent saturated thicknesses of the aquifer are about 300 m. The gravimetric survey held 500 new stations and found that the basin framework is quite irregular, with several positive and negative anomalies, similar to those present in grabens and horsts systems, related to the Transbrasilian lineament. The potentiometric map was generated by ordinary kriging, using the linear model (isotropic and anisotropic) and using parameters defined by variograms fitted to the spherical model (anisotropic). Comparing the estimated values with those measured, it was found that the kind of theoretical model employed does not interfere in the result. The transmissivities determined for the aquifer from the interpretation of 58 pumping tests presented large variation, with values ranging from 3.55 x 10-2 to 1.01 x 10-1 m2/h. The water balance was used to estimate the amount of water available for groundwater recharge, that was valued at 2.8 x 10-9 m3, representing about 22% of the annual average rainfall in the area. The permanent reserve of Serra Grande aquifer was estimated at 113 x 109 m3, while its potentiality or exploitable reserve is about 11.6 x 109 m3/year. The systematic view, which is the basis of this study, improved the scientific understanding of the aquifer, without which is not possible to manage it properly. It is hoped that the presented data will improve the proper use of water resources in the area, and consequently, the sustainable socioeconomic development of the region.